Influence of gender, neuter status, and training method on police dog narcotics olfaction performance, behavior and welfare - Fattah, Azhar F Abdel; Hamid, Shereen El Abdel (Journal of Advanced Veterinary and Animal Research, 2020)
Objective: This study was carried out to study the influence of gender, neuter status, and training method on police dog narcotics olfaction performance, behavior, and welfare. Materials and Methods: A total of 120 German Shepherds aged 1–3 years were used for this study. The dogs were separated into two experiments. The first experiment (32 dogs and 28 bitches) was used to study the influence of gender on olfaction and smell to narcotics in police dog performance and training methods with behavioral problems and welfare. The second experiment (30 dogs and 30 bitches) was used to study the influence of sexual status (entire or neutered) on the smelling of narcotics in police dog performance by comparing with intact dogs and bitches. Results: We found that there were significant differences in sex in training to detect narcotics. Male German Shepherds were found to be significantly more trainable than females. Neutering causes a difference in trainability in male and female dogs. Gonadectomy had adverse effects on training. The intact male and female German Shepherds were found to be significantly more trainable than the neutered ones, and the reward-based method was found to be significantly more trainable than punishment. Dog training methods incorporated by punishment result in pain, suffering, emotional instability, symptoms of depression, aggression, unwanted barking, growling at other people, not under control all time, less trainability, increased problematic behavior, and decreased dog welfare. Conclusion: Reward-based method is associated with lower lousy behavior and dogs with good behavior, such as, attachment attention behavior, dogs under the control of handler all times, higher trainability, less problematic behavior, and increased dog welfare. J. Adv. Vet. Anim. Res., 7(4): 655-662, Dec 2020 http://doi.org/10.5455/javar.2020.g464